Research on the Motivation and Risk of the Chinese Concept Stocks Return - MA, Yuemeng (2019)
Since the 1990s, with limited financing channels of Internet companies in China, a large number of small and medium-sized companies have gone public in the US. However, foreign investors have different cognition on the China Internet business model and philosophy, which restricts the expansion and sustainable development of the Chinese concept stocks. With the rapid growth of China's economy and policy support, China Stocks began to choose privatization and delisting to return to the Chinese market.